1939
DOI: 10.1042/bj0330249
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the metabolism of pyruvic acid in normal and vitamin B1-deficient states

Abstract: Criticisms of some of the previous methods are to be found in references marked with an asterisk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

1942
1942
1963
1963

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(19 citation statements)
references
References 5 publications
1
18
0
Order By: Relevance
“…Markees (1951b) has shown that boiling the filtrate for five minutes destroys the aceto-acetic acid (the main competitor of pyruvic acid) without loss of pyruvic acid. Normal Values.-The normal values for blood pyruvic acid in healthy persons obtained in this study (0.53-1.08 mg. %) are in conformity with other reports irrespective of the methods used (Bueding, Wortis, and Stern, 1942;Friedemann and Haugen, 1943;Lu, 1939;Markees, Kaser, and Lanz, 1950).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Markees (1951b) has shown that boiling the filtrate for five minutes destroys the aceto-acetic acid (the main competitor of pyruvic acid) without loss of pyruvic acid. Normal Values.-The normal values for blood pyruvic acid in healthy persons obtained in this study (0.53-1.08 mg. %) are in conformity with other reports irrespective of the methods used (Bueding, Wortis, and Stern, 1942;Friedemann and Haugen, 1943;Lu, 1939;Markees, Kaser, and Lanz, 1950).…”
Section: Discussionsupporting
confidence: 92%
“…Since newer methods for its estimation have been introduced by Lu (1939) and by Friedemann and Haugen (1943), several authors have studied the role of pyruvic acid in heart diseases (Altschule and Rosenfeld, 1947;Barenghi, Scarlotti, and Scafidi, 1941;Lasch, 1952;Torre, Teece, and Baldantoni, 1950;Yanof, 1942), and a survey of the changes in pyruvic acid levels in other diseases and in relation to therapy has been published by Markees (1951a).…”
mentioning
confidence: 99%
“…Pyruvate in the blood was estimated by a modification, partly suggested by Dr. E. S. Guz' man Barron, of the method of Lu (8). Lactate and pyruvate in the blood were stabilized with fluoride and iodoacetic acid.…”
Section: Methodsmentioning
confidence: 99%
“…The d~ uptake was measured, as usual, in Warburg-Barcroft manometers and vessels. Pyruvate was determined colorimetrically by a modification of the method of Lu (14). In experiments in which the pyruvate content of Arbacia eggs was determined, the eggs were centrifuged and 4 volumes of 20 per cent trichloroacetic acid were added.…”
Section: Methodsmentioning
confidence: 99%